Estimation of friction during equal channel angular (ECA) pressing of aluminum alloys - Shan, AD; Moon, IG; Park, JW (ELSEVIER SCIENCE SA, 2002)
Equal channel angular (ECA) pressing is a novel process to obtain an ultra-fine grain size in alloys and compounds through severe plastic deformation. However, severe friction occurs during such pressing. In this report, pure aluminum and an AlMgSi alloy were processed by ECA pressing and the load was recorded. The mechanical properties of the alloys before and after different passes during processing were measured by the tensile test. The relationship between the flow stress and the material properties are discussed. The results show that a properly designed die will give less friction. From this experiment, it is suggested that the exit channel of the ECA pressing die should be designed to be as short as possible, as long as the channel is strong enough to ensure ECA pressing. These results confirm that ECA pressing is a promising process that can be conducted under low pressure. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: DEFORMATION; SHEAR